Semiconductor sensors in physico-chemical studies - Kupriyanov, L. Yu (Elsevier, 1996)
The scientific basis of the technique of semiconductor chemical sensors is the main focus of this work. The book concentrates on the usage of semiconductor sensors in precision physico-chemical studies. The physical and chemical principles underlying the semiconductor sensor method are explained in detail. The mechanism of the processes occurring under the interaction of gas with semiconductor adsorbent surfaces are also discussed. Scientists and engineers specializing in the physics/chemistry of heterogeneous and heterogeneous-homogeneous processes and design of semiconductor chemical sensors will find the book of significant value.
Keywords: Chemical detectors.; Semiconductors.; elektronické knihy; electronic books